2003
DOI: 10.1080/10641734.2003.10505145
|View full text |Cite
|
Sign up to set email alerts
|

Celebrity Images in Magazine Advertisements: An Application of the Visual Rhetoric Model

Abstract: This paper applies the visual rhetoric model to celebrity gender images in magazine advertising. A content analysis of 207 ads containing celebrity endorsers was conducted. Results suggest that male celebrities are associated more with a visual plus verbal presentation mode and with functional product benefits. Conversely, female celebrities are associated more with a visual only presentation mode and psychosocial product benefits. Both theoretical and practical implications are ofered, along with future resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…Celebrities can take the role of spokesperson, endorsement, actor and testimonial (Erdogan, 1999). In the words of Stafford et al (2003), a celebrity endorser is “a famous person who uses public recognition to recommend or co-present with a product in an ad”. Celebrity refers to an individual who is known to the public, such as actors, sports figures, entertainers and others for their achievements in their respective areas other than the product endorsed by them (Friedman and Friedman, 1979).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Celebrities can take the role of spokesperson, endorsement, actor and testimonial (Erdogan, 1999). In the words of Stafford et al (2003), a celebrity endorser is “a famous person who uses public recognition to recommend or co-present with a product in an ad”. Celebrity refers to an individual who is known to the public, such as actors, sports figures, entertainers and others for their achievements in their respective areas other than the product endorsed by them (Friedman and Friedman, 1979).…”
Section: Review Of Literaturementioning
confidence: 99%
“…This investigation uses content analysis to define and generate a typology of aviation curriculum models and to determine the core content and intended outcomes at an aggregate level. Research on communication has shown content analysis to be an effective means to generate understanding (Kassarjian, 1977;Spears, 2001;Stafford, Spears, & Chung-kue, 2003). Content analysis effectively examines intended messages based upon frequency of discrete written content provided by a person or organization Kassarjian, 1977;Spears, 2001).…”
Section: Methods and Analysismentioning
confidence: 99%
“…For this reason, sports stars have come to have a huge influence over consumers' decisions, and consequently, sports star‐oriented marketing strategies have become prevalent (Stafford et al, ; Bush et al ; Lear et al, ; Boyland et al, ). While many companies employ sports stars in their marketing communications, these stars are not always beneficial assets for their sponsors.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%